Notch and Wnt signals cooperatively control cell proliferation and tumorigenesis in the intestine. - Fre, S.; Pallavi, S.K.; Huyghe, M.; Laé, M.; Janssen, K.P.; Robine, S.; Artavanis-Tsakonas, S.; Louvard, D. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Notch and Wnt signals play essential roles in intestinal development and homeostasis, yet how they integrate their action to affect intestinal morphogenesis is not understood. We examined the interplay between these two signaling pathways in vivo, by modulating Notch activity in mice carrying either a loss- or a gain-of-function mutation of Wnt signaling. We find that the dramatic proliferative effect that Notch signals have on early intestinal precursors requires normal Wnt signaling, whereas its influence on intestinal differentiation appears independent of Wnt. Analogous experiments in Drosophila demonstrate that the synergistic effects of Notch and Wnt are valid across species. We also demonstrate a striking synergy between Notch and Wnt signals that results in inducing the formation of intestinal adenomas, particularly in the colon, a region rarely affected in available mouse tumor models, but the primary target organ in human patients. These studies thus reveal a previously unknown oncogenic potential of Notch signaling in colorectal tumorigenesis that, significantly, is supported by the analysis of human tumors. Importantly, our experimental evidence raises the possibility that Notch activation might be an essential initial event triggering colorectal cancer.